Influence of genetic polymorphisms on fibrinogen level at taking of combined oral contraceptives - D. R. Gamyrkina; N. A. Vorobyova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2016)
The purpose of this study is to examine the influence of genetic polymorphisms of hemostasis system and age on the level of fibrinogen in patients against taking of combined oral contraceptives (COCs). As the results of our study, taking COCs has no significant effect on the level of fibrinogen. Other factors that increase the level of fibrinogen within the reference values: age and homozygous state of polymorphisms infibrinogen genes (455 A/A), platelet receptors GP IIb/IIIa (1565 C/C) and methylenetetrahydrofolate reductase (677 T/T).